SPIRITUALITY OF GENDANG RITUAL OF DEATH PERFORMED BY THE KARO ETHNIC PEOPLE IN THE GLOBALISATION ERA - Ginting, Pulumun Peterus; Ratna, I Nyoman Kutha; Suastika, I Made Suastika; Dibia, I Wayan Dibia (E-Journal of Cultural Studies, 2015)
The gendang ritual of death, which is performed by the Karo ethnic people, has changed a lot in regard to its spirituality in the globalization era. Such change, which has caused the gendang ritual of death to be secularized, results from the interaction between the local cultural elements and the global cultural ones; meaning that a new form and meaning have appeared. This present study is intended to identify, analyze and explain what such change is like, the factors contributing to it and its implication. This present study was designed as a qualitative study using the critical interdisciplinary and multidimensional approach of cultural studies. The theory of deconstruction, the theory of comodification, and the theory of semiotics were used to answer such questions. The data were analyzed descriptively, qualitatively, and interpretatively. The data were collected through observation, in-depth interview, documentary study, and library research. Three conclusions were inferred from the present study. First , the form of the change in spirituality of the gendang ritual of death performed by the Karo ethnic people in the globalization era; second , the factors contributing to such change; third , the meaning of such change. The study shows that the interaction between the local culture and global culture has marginalized the local cultural values; as a result, such a ritual has a new meaning, and is becoming degraded and secularized.
Keywords: Spirituality, gendang ritual of death, Karo ethnic group, and globalization era